Analysis on the residuals in GPS measurement due to tropospheric effect at the equatorial region - Yahya, Mohd. Hafiz (2008)
Global Positioning System (GPS) has been widely used by professionals and practitioners to support diverse applications such as navigation, surveying, mapping and engineering purposes. However, for highly precise applications (i.e. landslide detection, petrology and high rise structural monitoring) the key limitations currently facing this satellite-based positioning system is the signal propagation delay caused by the effect of troposphere where most of world's weather takes place. The effect is much more pronounced in Malaysia as it is located at the equatorial region where the troposphere extends up to 16 km above the earth surface. High humidity climate within the nation exaggerates the effect even further. This paper leads to an understanding on residuals in GPS measurement due to tropospheric effect at the equatorial region. Based on series of GPS observation made within Johore RTK Network (which is located in the equatorial region), it is obvious that tropospheric effect leads to variations or uncertainties in GPS measurement. Result shows that by neglecting the use of a standard tropospheric model, maximum residuals in Easting, Northing and Height components due to tropospheric effect are 68.880 cm, 68.970 cm and 119.100 cm respectively. Similarly, reaching to the minimum and maximum RMS value of 16.8 and 29.2 respectively, GPS Height component is by far the most affected component compared to the Horizontal components (Easting and Northing). Based on comparative study between short (UTMJHJY) baseline and long (UTM-MERS) baseline, result shows that the tropospheric effect is a distance-dependent error that increases when the baseline length between two GPS stations increases. Better result in the derived position is therefore can be expected from short GPS baseline compared to the long baseline.